On the Vectorization of FIR Filterbanks. (29th October 2006) - Barbedo Barbedo, Jayme Garcia Arnal Jayme Garcia Arnal; Lopes Lopes, Amauri Amauri
Abstract : This paper presents a vectorization technique to implement FIR filterbanks. The word vectorization, in the context of this work, refers to a strategy in which all iterative operations are replaced by equivalent vector and matrix operations. This approach allows that the increasing parallelism of the most recent computer processors and systems be properly explored. The vectorization techniques are applied to two kinds of FIR filterbanks (conventional and recursi ve), and are presented in such a way that they can be easily extended to any kind of FIR filterbanks. The vectorization approach is compared to other kinds of implementation that do not explore the parallelism, and also to a previous FIR filter vectorization approach. The tests were performed in Matlab andC, in order to explore different aspects of the proposed technique.